The case for considering volar skin in a “separate status” for wound healing - Tam, Joshua (Frontiers in Medicine, 2023)
Foot ulcers, particularly in the diabetic setting, are a major medical and socioeconomic challenge. While the effects of diabetes and its various sequelae have been extensively studied, in the wound field it is commonly assumed that the wound healing process is essentially identical between different skin types, despite the many well-known specializations in palmoplantar skin, most of which are presumed to be evolutionary adaptations for weightbearing. This article will examine how these specializations could alter the wound healing trajectory and contribute to the pathology of foot ulcers.